Os programas de transferência de renda do Brasil e do Uruguai e as organizações internacionais - Di Fiori, Gecira (2008)
The programmers for the transfer of income to combat poverty, adopted by the governments of Brazil and Uruguay, as a reproduction of economic power, ideological and political neo liberalism, articulated by international organizations, with particular Summit of the Americas to make up the object of this study. The objective of the research is to contribute to the debate on the path of the left in Latin America face of poverty and its close relationship with the adoption of measures that characterize point and targeted social policy in the current model of capitalist accumulation. The content is based on the interpretation of tradition Marxist thought and theoretical framework that supports this study is composed of political scientists, historians and researchers, from a theoretical perspective-critical problematical the actions of the governments of the left in the implementation of these programmers, focusing Latin America and its challenges of integration. To analyse and interpret the breeding and a. Maintenance of the principles programmatic conservatives in the fulfillments of international covenants and commitments election, the left-wing governments of Brazil and Uruguay, appealed to the analysis of the Declarations and Plans of Action of the Summits of the Americas and programmers of Government of Brazil (Lula Coalition again with the strength of the people) and Uruguay (Frente Amplia) and it was used the method of analysis of Content, (MORAES, 1999), of the plans of actions of the Summits of the Americas (OAS) and programmers of government in Brazil and Uruguay. Is selected categories, classified by the size economic, and social policies, which establish direct relations on the basis of criteria and semantic syntactical, whose description of the present set of meanings in different units of analysis (MORAES, 1999). Through this methodology and of the deepening of analysis of these units, one becomes related the programs of transference of income for the combat to the poverty, adopted for the governments of Brazil and Uruguay, with the influence of the economic, ideological power and neoliberal politician as well as its use to catch international resources. It is considered that the debate on programs of transference of income adopted by the governments of left of Brazil and Uruguay surpasses the limits of the divergence between capitalist models and the conception of the disentailed poverty of the objective relations of production and concentration of income.